Home Office: Perception of Employees and Manager of an Accounting Company in the Covid-19 Pandemic (Research, Society and Development, 2022)
The Covid-19 pandemic has generated several impacts in the social, economic, and political spheres. The social isolation as a preventive measure against the coronavirus has led organizations to restructure themselves, changing the way they perform their work activities, adhering to the home office. Given this scenario, the article has the premise of identifying the consequences of home office work, in the aspects of quality of life and productivity, both for the accounting organization and its employees, regarding the possible advantages and disadvantages of this work model, in the perception of the employees and the manager, in an accounting organization in the city of São Sebastião do Caí. A descriptive, exploratory, qualitative and quantitative research was carried out, in a case study. The results show that the home office was beneficial to the company during the epidemic peak, but that with the gradual decline of the pandemic, remote work lost its importance. It was also evidenced that, for the employees, there are more positive than negative points in relation to working in home office format, among them, the motivation and satisfaction, in which 52.17% said they felt motivated and satisfied, which possibly reflected in the commitment and productivity, since about 70% said they were committed and about 61%, responded that their productivity increased working in home office.